Quality of life following Minimally Invasive Direct Coronary Artery Bypass Grafting (MIDCABG) versus conventional open-heart coronary artery bypass grafting (CABG): a 3-year data from a single centre / Adli Azam Mohammad Razi, Muhammad ‘Abid Amir and Mohd Zamrin Dimon - Mohammad Razi, Adli Azam; Amir, Muhammad ‘Abid; Dimon, Mohd Zamrin (Faculty of Medicine, 2021)
In Malaysia, MIDCABG started in 3 centers developing the technique. As the technique is gaining traction in the country, this study aims to compare the quality of life following MIDCABG compared with conventional CABG in one of the centers actively developing this technique. Methods: A retrospective cohort study was performed involving 30 post CABG patients which consists of 15 MIDCABG and 15 conventional CABG from January 2015 to May 2018. 15 from 21 post-MIDCABG patients were included and selected, based on EuroSCORE II less than 5. Modified Post-Operative Quality of Recovery Scale was used to assess and compare the quality of life following respective approaches. Data were analyzed using SPSS version software and comparison using mean rank with p<0.05 as statistically significant. Results: The mean rank for pain score within 5 days, weeks of analgesics requirement and emotional status post operation for MIDCABG is higher. Both procedures have same mean rank for ability to walk without assistance postoperatively. Mean rank for daily activities 1 month after operation, ability to walk without assistance and ability to have good sleep is lower in MIDCABG. The mean rank for weeks to regained normal appetite and overall satisfaction of surgery for MIDCABG is higher. no significant different in the entire measured postoperative outcome between both operations as P > 0.05. Conclusion: There is no significant difference in quality of recovery following MIDCABG compared to conventional CABG. Modified PostOPQRS system can be a useful assessment tool to evaluate the impact of an intervention in relation of quality of life.